2017
DOI: 10.12795/elia.2017.i17.07
|View full text |Cite
|
Sign up to set email alerts
|

Tool usage and effectiveness among L2 Spanish computer writers

Abstract: This study describes the tools employed by intermediate learners of Spanish (N =12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The design described below closely follows that of O'Neill (2016), with the addition of two new elements: the use of online dictionaries by two of the groups (O'Neill focused only on online translation) and a Delayed Posttest (which was absent from O 'Neill, 2016). The study also differs from previous work such as Steding (2009), which focused on ethical issues and preventing online translation use; Tight (2017), which discussed instructing students about strengths and weaknesses of OTs but did not involve subsequent comparison of OT use with students using ODs or no tool; White and Heidrich 2013, which was an experimental study, but looked only at post-editing of online translation output, not at the effects of training or differences between OTs and ODs; and Wuttikrikunlaya et al (2018), another experimental study in which students could use any tool they chose, but which did not seek to tease out the impact of each tool individually on student writing. The current study's design was approved by the author's Institutional Review Board (IRB), ensuring the appropriateness of the protocol used and the informed consent of participants in human subjects research.…”
Section: Methodsmentioning
confidence: 80%
“…The design described below closely follows that of O'Neill (2016), with the addition of two new elements: the use of online dictionaries by two of the groups (O'Neill focused only on online translation) and a Delayed Posttest (which was absent from O 'Neill, 2016). The study also differs from previous work such as Steding (2009), which focused on ethical issues and preventing online translation use; Tight (2017), which discussed instructing students about strengths and weaknesses of OTs but did not involve subsequent comparison of OT use with students using ODs or no tool; White and Heidrich 2013, which was an experimental study, but looked only at post-editing of online translation output, not at the effects of training or differences between OTs and ODs; and Wuttikrikunlaya et al (2018), another experimental study in which students could use any tool they chose, but which did not seek to tease out the impact of each tool individually on student writing. The current study's design was approved by the author's Institutional Review Board (IRB), ensuring the appropriateness of the protocol used and the informed consent of participants in human subjects research.…”
Section: Methodsmentioning
confidence: 80%
“…More recent research has extended this work to consider how learners use computers to write (e.g., Elola et al, 2008; Severinson Eklundh & Kollberg, 1996) using actual computer recordings of writing task completion (e.g., Kessler, 2020; Levy & Ransdell, 1994; Schumacher et al, 1984). Overall, this research has shown that L2 writers use online tools widely, idiosyncratically, and for a variety of purposes (Elola et al, 2008; Lai & Chen, 2015; Tight, 2017; Yoon, 2016a, 2016b). Online tool usage leads L2 writers to varied levels of success based on numerous factors (Caws et al, 2017), such as understanding of tool affordances (Yoon, 2016b) and metalinguistic knowledge (Elola et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 93%
“…One set of tools that has received limited attention are MT tools–tools that rely on software to automatically translate text from one language to another (Qun & Xiaojun, 2015, p. 105). Indeed, only a handful of computer‐tracking studies have looked at MT and writing (e.g., Garcia & Pena, 2011; Tight, 2017). For example, Tight, (2017) used screen recording and recalls to observe how L2 learners of Spanish interacted with online tools, finding that while learners used these tools, including MT, frequently, their success related to different factors, such as knowledge of the home language.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the results of the learning process could be negatively affected by using these types of technology. Research subjects who took part in (Tight's 2017) examination of Spanish language students' employment of digital writing tools commented that novice writers frequently needed better work. The researcher is confident that extra instructional input is required to improve the efficacy of the technologies currently being utilized.…”
Section: Tips and Tools For Writing In The Digital Agementioning
confidence: 99%